Clinical and Economic Impact of Adopting Noninvasive Prenatal Testing as a Primary Screening Method for Fetal Aneuploidies in the General Pregnancy Population - Kostenko, Emilia; Chantraine, Frederic; Vandeweyer, Katleen; Schmid, Maximilian; Lefevre, Alex; Hertz, Deanna; Zelle, Laura; Bartha, Jose Luis; Di Renzo, Gian Carlo (Fetal diagnosis and therapy, 2019)
OBJECTIVE: To evaluate the clinical and economic impact of adopting noninvasive prenatal testing (NIPT) using circulating cell-free DNA as a first-line screening method for trisomy 21, 18, and 13 in the general pregnancy population. METHODS: A decision-analytical model was developed to assess the impact of adopting NIPT as a primary screening test compared to conventional screening methods. The model takes the Belgium perspective and includes only the direct medical cost of screening, diagnosis, and procedure-related complications. NIPT costs are EUR 260. Clinical outcomes and the cost per trisomy detected were assessed. Sensitivity analysis measured the impact of NIPT false-positive rate (FPR) on modelled results. RESULTS: The cost per trisomy detected was EUR 63,016 for conventional screening versus EUR 66,633 for NIPT, with a difference of EUR 3,617. NIPT reduced unnecessary invasive tests by 94.8%, decreased procedure-related miscarriages by 90.8%, and increased trisomies detected by 29.1%. Increasing the FPR of NIPT (from < 0.01 to 1.0%) increased the average number of invasive procedures required to diagnose a trisomy from 2.2 to 4.5, respectively. CONCLUSION: NIPT first-line screening at a reasonable cost is cost-effective and provides better clinical outcomes. However, modelled results are dependent on the adoption of an NIPT with a low FPR.
Keywords: genetické testování; Decision Support Techniques; Genetic Testing; Noninvasive Prenatal Testing; lidé; Female; Uncertainty; nejistota; metody pro podporu rozhodování; Aneuploidy; analýza nákladů a výnosů; Pregnancy; těhotenství; aneuploidie; Cost-Benefit Analysis; neinvazivní prenatální testování; ženské pohlaví; Humans